Autocrine parathyroid hormone-like hormone promotes intrahepatic cholangiocarcinoma cell proliferation via increased ERK/JNK-ATF2-cyclinD1 signaling. Issue 1 (December 2017) - Tang, Jing; Liao, Yan; He, Shuying; Shi, Jie; Peng, Liang; Xu, Xiaoping; Xie, Fang; Diao, Na; Huang, Jinlan; Xie, Qian; Lin, Chuang; Luo, Xiaoying; et al.
Abstract Background and aims Intrahepatic cholangiocarcinoma (ICC) is an aggressive tumor with a high fatality rate. It was recently found that parathyroid hormone-like hormone (PTHLH) was frequently overexpressed in ICC compared with non-tumor tissue. This study aimed to elucidate the underlying mechanisms of PTHLH in ICC development. Methods The CCK-8 assay, colony formation assays, flow cytometry and a xenograft model were used to examine the role of PTHLH in ICC cells proliferation. Immunohistochemistry (IHC) and western blot assays were used to detect target proteins. Luciferase reporter, chromatin immunoprecipitation (ChIP) and DNA pull-down assays were used to verify the transcription regulation of activating transcription factor-2 (ATF2). Results PTHLH was significantly upregulated in ICC compared with adjacent and normal tissues. Upregulation of PTHLH indicated a poor pathological differentiation and intrahepatic metastasis. Functional study demonstrated that PTHLH silencing markedly suppressed ICC cells growth, while specific overexpression of PTHLH has the opposite effect. Mechanistically, secreted PTHLH could promote ICC cell growth by activating extracellular signal-related kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling pathways, and subsequently upregulated ATF2 and cyclinD1 expression. Further study found that the promoter activity of PTHLH were negatively regulated by ATF2, indicating that a negative feedback loop exists. Conclusions Our findings demonstrated that the ICC-secreted PTHLH plays a characteristic growth-promoting role through activating the canonical ERK/JNK-ATF2-cyclinD1 signaling pathways in ICC development. We identified a negative feedback loop formed by ATF2 and PTHLH. In this study, we explored the therapeutic implication for ICC patients.